2020
DOI: 10.1177/0013124520931458
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Among Classroom Emotional Climate, Social Self-Efficacy, and Psychological Health of University Students in Taiwan

Abstract: The purposes of this study were to explore the correlations among classroom emotional climate, student social self-efficacy, and student psychological health. This study treated 392 university students as the research participants. The results of the confirmatory factor analysis showed that the factor structure of classroom emotional climate and social self-efficacy had a good fit. The results showed that classroom emotional climate could significantly affect social self-efficacy, that social self-efficacy cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…The level of self-esteem is defined as the result of one’s real social acceptance or real social exclusion or rejection [ 5 ]. Adolescents with low self-esteem are not easily accepted by their classmates in school, and they are more likely to be separated from their peers and spend more time alone [ 19 , 20 ]. The efficiency of functioning in different social situations is associated with self-esteem [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level of self-esteem is defined as the result of one’s real social acceptance or real social exclusion or rejection [ 5 ]. Adolescents with low self-esteem are not easily accepted by their classmates in school, and they are more likely to be separated from their peers and spend more time alone [ 19 , 20 ]. The efficiency of functioning in different social situations is associated with self-esteem [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the self-efficacy subscales had a significant correlation with depression. Hong et al (21) demonstrated that the emotional climate of the classroom could have a significant impact on social self-efficacy and that social selfefficacy could predict self-esteem and depression. Marle et al (41) also discussed the role of self-efficacy as a protective factor against 44) discovered a negative correlation between anxiety, depression, and self-efficacy in children with malignant tumors, and that increasing self-efficacy could reduce anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is predictive of future behavior, and it can serve as the inducer or inhibitor of appropriate actions ( 20 ). Hong et al ( 21 ) acknowledged that the emotional climate of the classroom could have a significant impact on social self-efficacy, that social self-efficacy could significantly predict self-esteem and depression, and that self-esteem could significantly predict depression. Self-efficacy, a key element of social cognitive theory, appears to be an important variable because it affects students' motivation and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have shown that self-efficacy can influence individuals’ performance, work practices, and work attitudes ( Liu, 2019 ; Cepale et al, 2021 ). In the field of education, empirical studies have shown that teachers’ self-efficacy (e.g., classroom management efficacy, and teaching efficacy) can predict their job burnout and job satisfaction ( Aloe et al, 2014 ; Perera et al, 2021 ), whereas college students’ self-efficacy (e.g., academic self-efficacy, career decision-making self-efficacy, and social self-efficacy) can predict their academic performance, career choice commitment, and psychological wellbeing ( Chemers et al, 2001 ; Wang et al, 2006 ; Hong et al, 2021 ). By introducing self-efficacy to the field of entrepreneurship, Boyd and Vozikis (1994) developed the concept of entrepreneurial self-efficacy, namely, the level of an individual’s belief that they can successfully assume various entrepreneurial roles and complete various entrepreneurial tasks.…”
Section: Literature Reviewmentioning
confidence: 99%